# Solve differential equation

## Homework Statement

$\frac{dr}{dt}=r(u-r)$

## Homework Equations

i rewrote this as $\frac{dr}{dt}-ur=-r^2$

i think this is like bernoulli's equation

## The Attempt at a Solution

so i let $w=\frac{1}{r}$ so that $r=\frac{1}{w}$
this gives me

$\frac{dr}{dt}=-1w^{-2}\frac{dw}{dt}$

so now i have
$-w^{-2}\frac{dw}{dt}-uw^{-1}=-w^{-2}$

if i divide by $-w^{-2}$

then i get a linear differential equation

$\frac{dw}{dt}+uw=1$

the integrating factor is $e^{ut}$

so i get $w=\frac{1}{u}+w_0e^{-ut}$

from my definition of $w$ i have $w_0=\frac{1}{r_0}$ and $w=\frac{1}{r}$

so i get $r=\frac{ur_0}{r_0+ue^{-ut}}$

is this right?

## The Attempt at a Solution

Related Calculus and Beyond Homework Help News on Phys.org
lanedance
Homework Helper
check by differentiating and comparing to the original DE

note this equation is separable, so you could do it by direct integration

please explain how i would solve by separation.
thanks

lanedance
Homework Helper
$$\frac{dr}{dt}=r(u-r)$$

gives
$$\int \frac{dr}{r(u-r)}=\int dt$$

though even if you can solve the integral (partial fractions may be a good start) it may be difficult to get into an analytic function for r(t)

HallsofIvy
Homework Helper
$$\frac{dr}{dt}= r(u-r)$$
with u constant.

$$\frac{dr}{r(u-r)}= dt$$

Integrate the left side with respect to r and the right side with respect to t.

( I really hate it when lanedance gets in one or two minutes ahead of me but to have him first with exactly the same timestand- arrrgh!)

ok so i get
$\frac{ln(r)-ln(r-u)}{u}=t$

which i then manipulate (or try to at least ) to get:
$ln\frac{r}{r-u}=ut$

if this is correct then i think i can do:
$\frac{r}{r-u}=e^{ut}$

i know something is wrong cos i dont have $r_0$

im working through an example in jordan and smith (nonlinear ordinary differential equations)
so i know what the answer should be, im trying to get to it tho.
:(